Human capital and savings in an OLG economy with migration possibilities: A theoretical note - Dacuycuy, Lawrence B. (Animo Repository, 2014)
In a theoretical study by Stark, Helmenstein, and Prskawetz (1998), the presence of migration possibilities may increase human capital formation. This note verifies the robustness of the said result by introducing savings as a choice variable in an overlapping generations model with migration possibilities. Results indicate that human capital formation will still increase provided that certain technical conditions are met. © 2014 by De La Salle University, Manila, Philippines.